2020
DOI: 10.1111/iju.14341
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcomes of transurethral thulium laser enucleation versus bipolar transurethral resection for benign prostatic hyperplasia over a period of 12 months: A prospective randomized study

Abstract: To evaluate functional outcomes over a year for benign prostatic hyperplasia treated with thulium laser enucleation of the prostate or bipolar transurethral resection of the prostate. Methods: In this study, we prospectively included 140 patients who were treated for benign prostatic hyperplasia from April 2017 to February 2019. A randomization list was used for non-blind assignment to treatment groups (thulium laser enucleation of the prostate or bipolar transurethral resection of the prostate). The Internati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…We found the risk of bias for randomized clinical trials to be high for 3 studies 32 , 34 , 35 due to absence of allocation concealment (not reported by 2 studies 32 , 34 and lacking mention of blinding in the other). 1 study 31 had a moderate risk as the information provided was unclear.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…We found the risk of bias for randomized clinical trials to be high for 3 studies 32 , 34 , 35 due to absence of allocation concealment (not reported by 2 studies 32 , 34 and lacking mention of blinding in the other). 1 study 31 had a moderate risk as the information provided was unclear.…”
Section: Resultsmentioning
confidence: 92%
“…Comparative Studies Assessing Tm:YAG Prostate Surgery Versus TURP Four RCTs 31,32,34,35 and one retrospective study 33 in our meta-analysis compared sexual outcomes after either Tm:YAG assisted prostate surgery or TURP. 2 of these studies 31,34 used a TmLRP technique and the other three 32,33,35 used a TmLEP technique. 2 studies 31,34 were carried out in China and the others in Japan, Russia, and Poland.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A preliminary review of 6421 papers from various databases was conducted, and after a screening process, finally, 27 papers included in the analysis [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] and involved studies that were all two-by-two comparisons. Besides, the total number of literature on the comparison of HoLEP and TURP was 19 [ 11 , 12 , 13 , 14 , 16 , 17 , 18 , 22 , 23 , 24 , 25 , 26 , 27 , 29 , 30 , 31 , 32 , 33 , 34 ] and 5 [ 15 , 19 , 21 , 35 , 36 ] on ThuLEP and TURP respectively, and 3 on the comparison of HoLEP and ThuLEP [ 8 , 20 , 37 ]. The results of the literature screening process are shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%